As condições sócio-ambientais de áreas de preservação permanente na zona urbana de Uberlândia: aspectos paisagísticos e sociais - Borges, David Jackson Vieira (2005)
Environmental degradation refers to any activity that, directly or indirectly, causes damage to the environment and its many aspects. This research was aimed at carrying out a diagnosis of environmental conditions in permanently protected areas (PPAs) around the sources and along the banks of streams found in Uberlândia s (MG) urban area as well as to assess awareness of the population living around these areas regarding their relevance and conditions. The methodological focus used was both qualitative and quantitative, showing statistically collected data, but also analyzing it in a narrative and descriptive way. Theoretical references used were related to landscape ecology and environmental perception. Field work was carried out to achieve the goals. Data on the local landscape was collected and a structured questionnaire was applied to the population that lives around the areas to assess individuals awareness so that their opinions, attitudes and values regarding the analyzed PPAs could be found out. Both biotope mapping and interaction matrix were used to assess the environmental conditions of the analyzed PPAs. According to the results, it has been concluded that the sources and banks of streams in Uberlândia fall into the average and high degradation categories. The main problems are deforestation, inappropriate use and occupation of land, soil pollution caused by deposition of solid waste and water pollution caused by problems in sewage management. The population interviewed has shown to be aware of PPAs-related problems.